Growth Hormone-Releasing Hormone Antagonists Inhibit Growth of Human Ovarian Cancer - Papadia, A.; Schally, A. V.; Halmos, G.; Varga, J. L.; Seitz, S; Buchholz, S.; Rick, F.; Zarandi, M.; Bellyei, S.; Treszl, A.; Szalontay, L.; Lucci, J. A. (Hormone and Metabolic Research, 2011)
Epithelial ovarian carcinoma is the leading cause of cancer-related deaths among women with gynecologic malignancies. Antagonists of the growth hormone-releasing hormone (GHRH) have been shown to inhibit growth of various cancers through endocrine, autocrine, and paracrine mechanisms. In this study, we have investigated the effects of GHRH antagonists (GHRHa) in ES-2 human clear cell ovarian cancer and in UCI-107 human serous ovarian cancer in vitro and in vivo. We evaluated the expression of mRNA for GHRH receptor, the binding to GHRH receptors, in specimens of ES-2 ovarian cancer. We evaluated also the in vitro effects of GHRHa on ES-2 cells and the in vivo effect of 2 different GHRHa on ES-2 and UCI-107 tumors. Nude mice bearing xenografts on ES-2 and UCI-107 ovarian cancer were treated with JMR-132 and MZ-J-7-118, respectively. Tumor growth was compared to control. ES-2 cells expressed mRNA for the functional splice variant SV1 of the GHRH receptor. JMR-132 inhibited cell proliferation in vitro by 42% and 18% at 10 and 1 μM concentration, respectively. Specific high affinity receptors for GHRH were detected in ES-2 cancer samples. In vivo daily subcutaneous injections of GHRHa significantly reduced tumor growth compared to a control group in both animal models. Our results indicate that GHRHa such as JMR-132 and MZ-J-7-118 can inhibit the growth of human ovarian cancer. The efficacy of GHRHa in ovarian cancer should be assessed in clinical trials.
Keywords: ovary; cancer; growth hormone-releasing hormone antagonists